Strengthening National Regulations in Combating Cross-Border Trafficking: Empirical Approach and the Way Forward - Senewe, Emma Valentina Teresha; Revivo, Antonio; Maramis, Ronny Adrie (Hasanuddin Law Review, 2024)
At practical level, both nationally and internationally, various efforts have been made to deal with increasingly acute human trafficking. However, as it turns out in practice, all existing legal instruments have not had a deterrent effect and have broken the chain of human trafficking to this day. Even more so in Indonesia. This article focuses on examining the answer to the problem, namely the national policy to prevent human trafficking and the efforts that can be made to eradicate increasingly complex human trafficking. This qualitative study is related to the policy and implementation of international and national policies to address human trafficking in cross-country border legal research. This paper provides information on the latest trends in research. The results show that the current moment of globalization is witnessing an extraordinary movement of people, legitimate and illegitimate, across national and international borders. This global movement of people has created panic across borders. It manifests itself in strengthening border controls and tightening immigration laws as a threat to the nation-state's security